Perencanaan Distribusi Air di Desa Ciela Kecamatan Bayongbong - Rian Hidayatullah; Sulwan Permana (Institut Teknologi Garut, 2025)
Water use is one of the most vital aspects of human life, essential not only for household needs but also for public, economic, and social infrastructure. One such area is Ciela Village, located in Bayongbong District, which is currently facing problems of uneven water distribution. This study aims to design a water distribution network system using EPANET 2.0, analyze population growth data for the next ten years by comparing two projection methods—arithmetic and geometric—and calculate water demand from both domestic and non-domestic sectors based on the Planning Criteria of the Directorate General of Human Settlements, Ministry of Public Works and Housing. Data collection in this study used a descriptive qualitative method, which included population data, topographic maps, and administrative boundaries. Water discharge was measured using a simple method involving a stopwatch, ruler, and a calibrated container with a known volume. The results show that the projected population of Ciela Village in the next ten years will reach 7,091 people. The Cikahuripan spring, which serves as the main water source for the plan, is capable of meeting community needs until 2033, as evidenced by a measured discharge of 6.4 liters/second, while the required discharge for the next ten years is 5.327 liters/second. The proposed distribution network design uses HDPE pipes with a 6-inch diameter, and the selected pump type is a Vertical Multistage Centrifugal Pump CR 10-14, chosen based on the pump head calculation results from EPANET 2.0. The main storage reservoir requires a capacity of 552.268 m3, while the service reservoir requires a capacity of 51.421 m3. Overall, this study demonstrates that the Cikahuripan spring can sustainably support the projected water demand for the next decade and provides a technically sound plan for improving the water distribution system in Ciela Village.